2008
DOI: 10.3928/15428877-20080701-19
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Anterior Staphyloma with Dehydrated Dura Mater Patch Graft

Abstract: A case of postoperative large anterior staphyloma of the sclera was treated with a dehydrated cadaveric dura mater patch graft. Structural integrity of the globe and a good cosmetic result were obtained after the surgery. During the follow-up of 2 years, no recurrence of staphyloma developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…It is unable to withstand the intraocular pressure, and thus, progressively protrudes. The few treatment options in anterior staphyloma include penetrating keratoplasty, sclerokeratoplasty, and dural patch (6)(7)(8) . Besides increased complexity of large graft surgery resulting from loss of limbal support and subsequent protrusion of the lens-iris diaphragm during surgery, the poorer outcomes observed in these types of procedures are multifactorial, including extensive initial infection, postoperative chronic ocular surface and anterior segment inflammation, and secondary glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unable to withstand the intraocular pressure, and thus, progressively protrudes. The few treatment options in anterior staphyloma include penetrating keratoplasty, sclerokeratoplasty, and dural patch (6)(7)(8) . Besides increased complexity of large graft surgery resulting from loss of limbal support and subsequent protrusion of the lens-iris diaphragm during surgery, the poorer outcomes observed in these types of procedures are multifactorial, including extensive initial infection, postoperative chronic ocular surface and anterior segment inflammation, and secondary glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options in cases of anterior staphyloma include penetrating keratoplasty, mushroom grafts, sclerokeratoplasty, and du ral patch (6)(7)(8) . We report a case of acquired anterior staphyloma following perforation of a corneal ulcer in a patient who used crack cocaine daily for 6 months prior to the second presentation and its management.…”
Section: Introductionmentioning
confidence: 99%
“… 1 To reinforce thinned sclera, various materials have been attempted for grafting including allogeneic sclera, amniotic membrane (AM), fascia lata, dura mater, pericardium and periosteum. 2 – 6 However, an ectopic donor tissue such as periosteum, dura mater, or pericardium is hard to obtain; therefore, clinical experience with these has been limited. Among these materials, preserved donor scleral grafts have been preferred for a long time and have produced acceptable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…3 The treatment modalities available in cases of anterior staphyloma include penetrating keratoplasty, mushroom grafts, step grafts, sclerokeratoplasty, and dural patch. [4][5][6][7] The incidence of glaucoma after a routine keratoplasty varies from 9% to 31% in the early postoperative period and from 18% to 35% in the late postoperative period. 8 A study by Goldberg et al 9 found that 71% of patients with preexisting glaucoma had increased pressure develop in the early postoperative course.…”
mentioning
confidence: 99%